miRNA let-7f-5p-encapsulated labial gland MSC-derived EVs ameliorate experimental Sjögren’s syndrome by suppressing Th17 cells via targeting RORC/IL-17A signaling axis - Yufei Xie; Maosheng Chai; Yixiao Xing; Peiru Zhou; Pan Wei; Hong Hua (Journal of Nanobiotechnology)
Abstract Sjögren’s syndrome (SS) is an autoimmune disease primarily affecting salivary glands, with xerostomia as a distinct clinical manifestation. This disease also poses a significantly increased risk of lymphoma, severely impacting patients’ quality of life. The imbalance between Th17 and Treg cells plays a critical role in SS progression, driving severe immune dysregulation, chronic inflammation, and escalating tissue dysfunction. However, current clinical treatments for SS still remain limited, and it continues to be recognized as a refractory disease. Therefore, the development of novel and effective therapeutic strategies is a pressing demand in clinical research. In recent years, extracellular vesicle (EV) therapy has emerged as a promising approach for autoimmune disease treatment, showing encouraging outcomes in modulating immune balance and alleviating symptoms. EVs carry diverse cargo, among which microRNAs (miRNAs) are highly abundant and play critical roles. These small RNAs are essential for EV-mediated functions, particularly in regulating gene expression and modulating the immune microenvironment. Our research team first isolated labial gland mesenchymal stem cells (LGMSCs) and their derived EVs (LGMSC-EVs), which offer potential therapeutic advantages in SS due to their salivary gland origin. Then we screened and identified the highly enriched miRNA let-7f-5p as a key regulator through miRNA profiling analysis. To achieve better therapeutic outcomes, we transfected exogenous miRNA let-7f-5p into LGMSC-EVs to upregulate its expression, thereby constructing let-7f-5p-encapsulated LGMSC-EVs. These modified EVs were subsequently tested in an experimental SS mouse model to evaluate their therapeutic potential. The upregulation of miRNA let-7f-5p in LGMSC-EVs significantly enhanced their therapeutic effects, resulting in clinical improvements such as increased salivary flow and reduced lymphocytic infiltration. Mechanistically, let-7f-5p-encapsulated LGMSC-EVs suppressed Th17 cells by directly targeting the 3’-untranslated region (3’UTR) of RORC, inhibiting the RORC/IL-17A signaling axis, and reducing IL-17A production, thereby restoring Th17/Treg balance and promoting an anti-inflammatory profile. Collectively, this let-7f-5p-encapsulated LGMSC-EV therapy offers a promising target-driven approach for the treatment of SS, achieving improved clinical outcomes and immune rebalance after modification with miRNA let-7f-5p, which presents new potential for the clinical treatment of SS. Graphical Abstract